2002
DOI: 10.1079/nrr200241
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient cofactor research with extensions to applications

Abstract: Following identification of essential micronutrients, there has been a continuum of research aimed at revealing their absorption, transport, utilization as cofactors, and excretion and secretion. Among those cases that have received our attention are vitamin B 6 , riboflavin, biotin, lipoate, ascorbate, and certain metal ions. Circulatory transport and cellular uptake of the water-soluble vitamins exhibit relative specificity and facilitated mechanisms at physiological concentrations. Isolation of enzymes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 175 publications
(152 reference statements)
0
5
0
2
Order By: Relevance
“…Evidence for involvement of ATP as a ligand of zinc has been provided, thus demonstrating in principle how biological specificity by LMW species can be achieved. Some kinases phosphorylating vitamins prefer a ZnATP complex over a MgATP complex [57]. In the crystal structures of flavokinase and pyridoxal kinase a bound ZnATP complex was detected [58], [59].…”
Section: The Coordination Of Zinc In the “Free” Zinc Poolmentioning
confidence: 94%
“…Evidence for involvement of ATP as a ligand of zinc has been provided, thus demonstrating in principle how biological specificity by LMW species can be achieved. Some kinases phosphorylating vitamins prefer a ZnATP complex over a MgATP complex [57]. In the crystal structures of flavokinase and pyridoxal kinase a bound ZnATP complex was detected [58], [59].…”
Section: The Coordination Of Zinc In the “Free” Zinc Poolmentioning
confidence: 94%
“…ZnATP rather than MgATP is the preferred substrate for some kinases involved in cofactor biosynthesis: pyridoxal kinase, riboflavin kinase, and NAD kinase. X-ray structures of the first two enzymes indeed show the interaction with a ZnATP complex. , Noteworthy, MT activates pyridoxal kinase . An equilibrium dialysis showed that ATP removes Zn­(II) from MT.…”
Section: Relating Metallothionein Thermodynamics and Kinetics To Cont...mentioning
confidence: 99%
“…Pyridoxal kinase and riboflavin kinase, controlling cofactor biosynthesis, prefer a Zn-ATP over a Mg-ATP complex [98]. X-ray structures of these enzymes show the binding of a Zn-ATP complex [99,100].…”
Section: Zinc In Coenzyme Metabolismmentioning
confidence: 99%